PENGARUH KEBUGARAN JASMANI DAN INTERAKSI SOSIAL TERHADAP PRESTASI BELAJAR PENJASORKES SISWA KELAS TINGGI SD I DONOTIRTO KRETEK BANTUL - Sri Wahyuni (Dinas Pendidikan, Pemuda dan Olahraga Daerah Istimewa Yogyakarta, 2018)
This study is aimed at finding out: (1) the influence of physical fitness on physical education learning achievement of the upper grade students of SDN I Donotirto Kretek Bantul in the academic year of 2015/2016, (2) the influence of social interaction on physical education learning achievement of the upper grade students of SDN I Donotirto Kretek Bantul in the academic year of 2015/2016, and (3) the influence of physical fitness and social interaction (simultaneously) on physical education learning achievement of the upper grade students of SDN I Donotirto Kretek Bantul in the academic year of 2015/2016. This study was applied quantitative approach/method by using ex-post facto data. The subjects of this study were eighty students of the upper grade (grade IV – VI) of SDN I Donotirto Kretek Bantul Yogyakarta. The data were collected through physical education test for 10 – 12 years old students, questionnaires and documentations. The study used descriptive analytic and double regression calculation to analyze the data. The result of the descriptive analytic calculation shows that majority of the students (57.5%) were classified as deficient on physical fitness variable and 82.5% of the students were categorized as good/excellent on social interaction. The result of the regression calculation on physical fitness shows , tquantification = 9.067 with (significant). While the calculation result on students social interaction shows , tquantification = 3.7952 with (significant). The calculation results also show the determination coefficient R = 0.580, Fquantification = 50.076 with (significant). Based on the results in this study, it can be concluded that the students physical fitness and social interaction (partially or simultaneously) influence the physical education learning achievement of the upper grade students of SDN I Donotirto Kretek Bantul in the academic year of 2015/2016. The more active students on social interaction and the fitter the students’ body, the higher the learning achievement will be.